The happy couple : law and literature - R. West (Law Text Culture, 1995)
The Happy Couple: Law and Literature, J. Neville Turner and Pamela Williams, eds. Sydney, The Federation Press, 1994. The Happy Couple: Law and Literature, is a collection of thirty two papers (plus a quiz on Dickens), most of which were delivered at the second annual convention of the Australian Law and Literature Association, held at Monash University in 1991. In their Preface to the collection, the editors note that this is the first Australian collection of work in law and literature, and explain that it is, in their view, a representative sampling ofAustralian work in the field (xv). The book as a whole attests not only to the range of interests and subject matter, but also of disciplinary expertise and style covered by the Australian Law and Literature movement; as the editors suggest in their preface, there is truly something here for everyone (xvi).